Factors Influencing the Use of the MPDN Application by Midwives at RSU Boven Digoel Regency, Papua Province in 2023 - Merry G F Ulahayanan; Dede Sri Mulyana (CV. Inara, 2024)
Background:Maternal Perinatal Death Notification (MPDN) is a fast and structured maternal death reporting application, utilizing the latest information technology and has been used for 15 years in Indonesia. Purpose of Writing: to determine the factors that influence the use of the MPDN application by midwives. Research Methods: This type of quantitative research uses a cross sectional study design, the sample in this study is 35 people, test the chi square analysis. Research Results: There is a relationship between knowledge (p value=0.012) and training (p value=0.002) with the use of the MPDN application by midwives, there is no relationship between attitude (p value=0.849) and the availability of smart phones and internet connection (p value=0.656) with the use of the MPDN application by midwives. Conclusions and Suggestions: It is hoped that the results of this study will serve as material for consideration and evaluation of improving the quality of human resources and quality of hospital services, one of which is by using the latest informatics technology for reporting maternal and infant mortality / Maternal Perinatal Death Notification.